Cape Town Central Fire Station - Fitchett, Rowallan Hugh (School of Architecture, Planning and Geomatics, 2017)
The fire service is unique in providing for the whole community a form of protection that is beneficial to all. It does not serve any one group of people to the detriment of others, nor can it be manipulated to further political ends. It is an organisation with a highly developed sense of honour, which commands the respect of the people it serves. It also captures the imagination of the public. Its machines are flashy and exciting, its work vital and dynamic. Contact with the community is essential for the fire brigade, as the number of fires that break out can only be kept under control by increasing the awareness of the community. For this reason, the fire station must not only be a symbol of civic protection, it must be a building that actively reaches out to the people, and encourages them to participate in its activities. The existing central fire station was built in 1932, and its efficiency is now suffering in two respects. The growth of the brigade has resulted in unplanned expansion of the administrative section of the building, which has caused functional relationships between different activities to become disjointed. In addition, the senior officers feel that there are too many different activities taking place in the station for it to operate smoothly. As well as the normal fire station functions and administrative headquarters, the central station accommodates the workshops and training school which serve the whole brigade. To overcome these problems, the fire department plans to demote the present headquarters to the level of a sub-station serving the city centre, and to build a new central fire station in Paarden Eiland. In many ways this is an unfortunate decision. The executive, administrative and public-orientated activities will be isolated from the people they serve, and the associations of the central fire station forming a gateway to the city at the top of Roeland Street will be lost.